Sensitivity analysis and parameter estimation for an approximate analytical model of canal-aquifer interaction applied in the C-111 basin - Kisekka, Isaya; Migliaccio, K. W.; Munoz-Carpena, R.; Khare, Y.; Boyer, T. H. (My University, 2013)
The goal of this study was to better characterize parameters influencing the exchange of surface water in south Florida’s C-111 canal and Biscayne aquifer using the analytical model STWT1. A three-step model evaluation framework was implemented as follows: (1) qualitative parameter ranking by comparing two Morris method sampling strategies, (2) quantitative variance-based sensitivity analysis using Sobol’s method, and (3) estimation of parameter posterior probability distributions and statistics using the Generalized Likelihood Uncertainty Estimator (GLUE) methodology. Results indicated that the original Morris random sampling method underestimated total parameter effects compared to the improved global Morris sampling strategy. However, parameter rankings from the two sampling methods were similar. For the STWT1 model, only four out of the six parameters analyzed were important for predicting water table response to canal stage and recharge fluctuations. Morris ranking in order of decreasing importance resulted in specific yield (ASY), aquifer saturated thickness (AB), horizontal hydraulic conductivity (AKX), canal leakance (XAA), vertical hydraulic conductivity (AKZ), and half-width of canal (XZERO). Sobol’s sensitivity indices for the four most critical parameters revealed that summation of first-order parameter effects was 1.0, indicating that STWT1 behaved as an additive model or negligible parameter interactions. We estimated parameter values of 0.07 to 0.14 for ASY, 11,000 to 14,300 m d-1 for AKX, 13.4 to 18.3 m for AB, and 99.8 to 279 m for XAA. The estimated values were within the range of values estimated using more complex methods at nearby sites. The Nash-Sutcliffe coefficient of efficiency and root mean square error for estimated parameters ranged from 0.66 to 0.95 and from 4 to 7 cm, respectively. This study demonstrates a simple and inexpensive way to characterize hydrogeological parameters controlling groundwater-surface interactions in any region with aquifers that are highly permeable without using standard pumping tests or canal drawdown experiments. Hydrogeological parameters estimated using this approach could be used as starting values in large-scale numerical simulations.
Keywords: Canal-aquifer interaction; GLUE method; Morris method; Parameter estimation; Sensitivity analysis; Sobol’s method